(untitled) (Journal of Applied Oral Science, 2009)
OBJECTIVE: To evaluate the microhardness of resin-modified glass-ionomer cements (RMGICs) photoactivated with a blue light-emitting diode (LED) curing light. MATERIAL AND METHODS: Thirty specimens were distributed in 3 groups: Fuji II LC Improved/GC (RM1), Vitremer/3M ESPE (RM2) and Filtek Z250/ 3M ESPE (RM3). Two commercial light-curing units were used to polymerize the materials: LED/Ultrablue IS and a halogen light/XL3000 (QTH). After 24 h, Knoop microhardness test was performed. Data were submitted to three-way ANOVA and Tukey's test at a pre-set alpha of 0.05. RESULTS: At the top surface, no statistically significant difference (p>;0.05) in the microhardness was seen when the LED and QTH lights were used for all materials. At the bottom surface, microhardness mean value of RM2 was significantly higher when the QTH light was used (p;0.05) for both RMGICs, regardless of the light used. For RM3, microhardness mean value at the top was significantly higher (p